Strategy and Implementation of Religious Moderation in Islamic Education at UIN Sultan Maulana Hasanuddin Banten - Suherman Priatna; Ahmad Fitriyadi Sari (Center for Research and Community Service of UIN Sultan Maulana Hasanuddin Banten-Serang City-Indonesia, 2025)
This study examines the strategies and implementation of religious moderation within Islamic Education at UIN Sultan Maulana Hasanuddin Banten. Religious moderation has become a national priority in Indonesia to strengthen harmony, counter extremism, and promote peaceful coexistence. Using a qualitative descriptive approach, this research investigates institutional strategies, curriculum design, learning practices, and policy implementation at UIN SMH Banten. The findings reveal that the university integrates religious moderation through curriculum enrichment, lecturer capacity building, research activities, community service programs, and campus culture development. Challenges include varied student backgrounds, limited integration across all study programs, and the need for more systematic evaluation mechanisms. The implication study concludes that UIN SMH Banten has made significant progress in mainstreaming religious moderation, although continuous enhancement is necessary to strengthen its sustainability.